COSO ERM AND RISK MANAGEMENT - Sánchez Sánchez, Liliana Ruth (2015)
Considering that every entity faces various risks affecting different parts of the organization; management needs to not only handle individual risks but also understand the interrelated impacts. For this, the COSO ERM methodology was designed to identify potential events that affected an entity, evaluate and respond to identified risks, so that they are within the limits of acceptable level as part of a good management.The application of this methodology, helped identify the risks in the company and assessed the efficiency and effectiveness of the controls, so that the entity achieved the objectives.The research findings showed that the COSO ERM methodology identified and managed risks at the level of the entity; aligned the accepted risk level with the business’ strategy; it improved the decisions on risk response; it minimized surprises and operating losses; it provided integrated responses to multiple risks and opportunities especially took advantage of opportunities.